H2O2 and CH3OOH (MHP) in the Remote Atmosphere: 1. Global Distribution and Regional Influences. Issue 6 (18th March 2022) - Allen, Hannah M.; Crounse, John D.; Kim, Michelle J.; Teng, Alexander P.; Ray, Eric A.; McKain, Kathryn; Sweeney, Colm; Wennberg, Paul O.
Abstract: Atmospheric hydroperoxides are a significant component of the atmosphere's oxidizing capacity. Two of the most abundant hydroperoxides, hydrogen peroxide (H2 O2 ) and methyl hydroperoxide (MHP, CH3 OOH), were measured in the remote atmosphere using chemical ionization mass spectrometry aboard the NASA DC‐8 aircraft during the Atmospheric Tomography Mission. These measurements present a seasonal investigation into the global distribution of these two hydroperoxides, with near pole‐to‐pole coverage across the Pacific and Atlantic Ocean basins and from the marine boundary layer to the upper troposphere and lower stratosphere. H2 O2 mixing ratios are highest between 2 and 4 km altitude in the equatorial region of the Atlantic Ocean basin, where they reach global maximums of 3.6–6.5 ppbv depending on season. MHP mixing ratios reach global maximums of 4.3–8.6 ppbv and are highest between 1 and 3 km altitude, but peak in different regions depending on season. A major factor contributing to the global H2 O2 distribution is the influence of biomass burning emissions in the Atlantic Ocean basin, encountered in all four seasons, where the highest H2 O2 mixing ratios were found to correlate strongly with increased mixing ratios of the biomass burning tracers hydrogen cyanide (HCN) and carbon monoxide (CO). This biomass burning enhanced H2 O2 by a factor of 1.3–2.2, on average, in the Atlantic compared with the Pacific Ocean basin. Plain Language Summary: Hydroperoxides, a large class of compounds that contain the R–OOH chemical structure, exist in the gas phase in the atmosphere. These compounds are key to the chemistry of the atmosphere because of the role they play in the atmosphere's ability to process and ultimately remove chemical species. Two of the most abundant atmospheric hydroperoxides were measured as part of the Atmospheric Tomography Mission, which collected samples of the atmosphere over the Pacific and Atlantic Ocean basins far from human influences. This paper presents a summary of the global distribution of these hydroperoxides across the four different seasons (winter, spring, summer, fall) and investigates the role that smoke from large‐scale fires on the continents plays in altering the amount of atmospheric hydroperoxides above the Atlantic Ocean. Key Points: The Atmospheric Tomography Mission provides an unprecedented investigation into the global seasonal distribution of hydroperoxides Chemical Ionization Mass Spectrometry is a sensitive technique for studying hydroperoxides in the remote atmosphere Biomass burning emissions increase H2 O2 mixing ratios in the Atlantic Ocean compared to corresponding latitudes in the Pacific Ocean basin